Perencanaan Konstruksi Mesin Duplikat Kunci Pada Ahli Kunci Malang Hermanto - Purkuncoro, Aladin Eko; Hutabarat, Julianus; Kurniawan, Arif (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
A key duplicate machine is indispensable for daily needs. There are so many functions that we can get by having a key machine. One example is that we can duplicate the keys we have everyday, whether house keys, car keys, motorcycle keys, or so on. The method applied in the design of this key duplicate machine construction begins with concept design, presentation of drawings, and identification of tools and materials used in the design of the key duplicate machine construction consisting of 2 types of machines, namely: DEFU 339C and DEFU 238BS. This key duplicate machine is designed to help residents duplicate the keys of both tools and vehicles so that they are not hampered when doing activities and become more efficient because the process of making duplicate keys uses tools designed by showing aspects of cost, efficiency, and effectiveness. This tool uses a power source from an electric motor with a minimalist construction design but with a relatively cheap tool production cost with similar products sold in the market. The process starts from selecting the type of key material, then the key material is recorded on a duplicate machine along with the parent key with the same shape so that it is precise and functions properly.